Consumer confidence from Cluj-Napoca metropolitan area, in the food labeling system - Ioana Ancuța Iancu; Alexandru-Mircea Nedelea (Amfiteatru Economic Journal, 2018)
In order to discover the aspects that influence the consumer level of confidence (from ClujNapoca metropolitan area), regarding the information on the food label and their reading frequency a study based on a questionnaire was made. This was promoted online, especially on Facebook and was filled in by 392 persons. Besides the descriptive analysis meant to offer us an overview of the aspects that influence the consumer level of confidence regarding the information on the food label, the authors have proposed to observe the level of association and test some hypotheses, which are linked to the importance of some elements (sex, age, education, family income, buying food for children under 5 and over 6 years old, smokers, athletes, the perception of the correctness of information on the label, food poisoning, country of origin and the benefits of technology in food sector). The results indicate a decrease in the level of confidence of Romanian consumers in the information on the food label, while the age, the number of years spent on formal study, increased revenue and shopping of products for children under the age of 5 influence the frequency of label reading. On the other side, women grant a higher importance to the information that is mandatory, by law, to be included on the label, than men. This study shows the importance of improving the trust of consumers in the food labelling system by increasing the frequency of reading. We underline that information of consumers can't be successfully achieved if they don't read or trust the information found on the labels.
Keywords: M31; 330; Consumers' information; labels; the frequency of label reading; trust; food; adjusted residual values; χ² test